2008
DOI: 10.1016/j.ccr.2007.11.031
|View full text |Cite
|
Sign up to set email alerts
|

An E2F1-Dependent Gene Expression Program that Determines the Balance between Proliferation and Cell Death

Abstract: The Rb/E2F pathway regulates the expression of genes essential for cell proliferation but that also trigger apoptosis. During normal proliferation, PI3K/Akt signaling blocks E2F1-induced apoptosis, thus serving to balance proliferation and death. We now identify a subset of E2F1 target genes that are specifically repressed by PI3K/Akt signaling, thus distinguishing the E2F1 proliferative or apoptotic function. RNAi-mediated inhibition of several of these PI3K-repressed E2F1 target genes, including AMPK alpha 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
213
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 52 publications
8
213
0
Order By: Relevance
“…The top 66% (451 probes) of variable probes were then used to cluster the BFRM normalized Mas5 formatted gene expression data using complete linkage hierarchical clustering. Previously identified intrinsic subtypes were identified and the expression characteristics of each subtype were found to be consistent with previously published studies (4,13,6). Specifically, the HER2+ expression cluster was found to show high expression of genes in the 17q21 amplicon including HER2/ERBB2 and GRB7.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…The top 66% (451 probes) of variable probes were then used to cluster the BFRM normalized Mas5 formatted gene expression data using complete linkage hierarchical clustering. Previously identified intrinsic subtypes were identified and the expression characteristics of each subtype were found to be consistent with previously published studies (4,13,6). Specifically, the HER2+ expression cluster was found to show high expression of genes in the 17q21 amplicon including HER2/ERBB2 and GRB7.…”
Section: Methodssupporting
confidence: 71%
“…Other relationships, not necessarily anticipated from past work, are also evident in this analysis including coactivation of E2F1 and PI3K pathways together with β-catenin. Interestingly, E2F1 is known to act as a signal for p53-dependent apoptosis, which is negated by PI3K activity (13). Finally, other patterns are evident including AKT/p63/ SRC as well as EGFR/TGFβ and STAT3/TNFα.…”
Section: Patterns Of Pathway Activity Characterize the Diversity Of Bmentioning
confidence: 94%
“…up-regulates the expression of SVV, most likely through a previously reported direct interaction with the SVV promoter, 42,43 thereby contributing to the invasive potential of BC cells.…”
Section: Discussionmentioning
confidence: 92%
“…Activation of AMPK induces p53-dependent apoptotic cell death in response to energetic stress [37]. Moreover, AMPK activation with AICAR further enhances E2F1-mediated apoptosis [38]. All these studies suggested that AMPK activation could play a pro-apoptotic role in different types of cells.…”
Section: Discussionmentioning
confidence: 95%